C3 N-A 2D Crystalline, Hole-Free, Tunable-Narrow-Bandgap Semiconductor with Ferromagnetic Properties - Yang, Siwei (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.